The Money Exchange Dealers of Kabul : A Study of the Hawala System in Afghanistan - Munzele Maimbo, Samuel (Washington, DC: World Bank, 2013)
Money convenient, and inexpensive means of transferring funds into Afghanistan and among its provinces. They offer a diverse range of financial and non-financial business services at the local, regional, and international level. More recently, they have been instrumental in providing financial services for the delivery of emergency relief and humanitarian and developmental aid into Afghanistan for the majority of international and domestic NGOs, donor organizations, and development aid agencies. This study was undertaken to: (1) determine the current practice of hawala in Afghanistan; (2) verify the assertions regarding the convenience, speed, and cost-effectiveness of hawala transactions in comparison with formal financial institutions such as the central bank and the remaining state banks; (3) evaluate the use of money exchange dealers to remit development funds to regions that are not served by formal financial institutions; (4) identify the operational characteristics that make the hawala system vulnerable to financial abuse; and (5) consider the appropriate regulatory and supervisory options for informal funds transfer systems in Afghanistan.